To find the value that correctly fills in the blank so that the expressions are equivalent, we will first calculate the left side of the equation.
Let's start with the expression on the left:
\[ 42 + 70 \]
Calculating this, we get:
\[ 42 + 70 = 112 \]
Now we move on to the expression on the right side, which is:
\[ (6 + 10) \]
Calculating this, we have:
\[ 6 + 10 = 16 \]
Now, we see that we need to set the right side equal to the value we found on the left side:
\( (6 + 10) \) is equivalent to 16, and we want to find a value that can fill the blank to make it equivalent to 112.
If we represent the blank as \( x \), we look for an expression that will produce 112 when filled:
\[ (6 + 10) + x = 112 \]
Since \( 6 + 10 = 16 \), we can substitute that into the equation:
\[ 16 + x = 112 \]
To find \( x \), we subtract 16 from both sides:
\[ x = 112 - 16 \] \[ x = 96 \]
Therefore, the value that correctly fills in the blank is
\[ \boxed{96} \]